Sosialisasi Penggunaan Microsoft Excel untuk Pembukuan Sederhana Pada Usaha Indekos Simak Rowolaku - Dina (PT Kimshafi Alung Cipta, 2026)
In the growing digital era, the use of information technology and software has become very important in various aspects of life, including in financial management and bookkeeping. One software that is popular and often used for this purpose is Microsoft Excel. Microsoft Excel has become one of the most commonly used tools in simple bookkeeping in various types of businesses. The purpose of this community service is to provide an understanding of the use of Microsoft Excel for simple bookkeeping. This community service method is in the form of socialization in which later the community can understand, study, and practice community values in the form of social behavior, so that they can be accepted by their environment. The service team will provide instructions or practices on how the owner of the Simak boarding house should do bookkeeping using Microsoft Excel. The service team provides the best briefing related to the process of making simple bookkeeping. The results of this socialization show that business actors realize the importance of bookkeeping in carrying out economic activities, so that it can be implemented in real business or personal financial management. Simple bookkeeping which includes regular data collection procedures and recording financial information can be applied in Microsoft Excel effectively and can be accessed anywhere.